Nonequilibrium Lattice Dynamics in Photoexcited 2D Perovskites. Issue 44 (3rd October 2022) - Cuthriell, Shelby A.; Panuganti, Shobhana; Laing, Craig C.; Quintero, Michael A.; Guzelturk, Burak; Yazdani, Nuri; Traore, Boubacar; Brumberg, Alexandra; Malliakas, Christos D.; Lindenberg, Aaron M.; Wood, Vanessa; Katan, Claudine; et al.
Abstract: Interplay between structural and photophysical properties of metal halide perovskites is critical to their utility in optoelectronics, but there is limited understanding of lattice response upon photoexcitation. Here, 2D perovskites butylammonium lead iodide, (BA)2 PbI4, and phenethylammonium lead iodide, (PEA)2 PbI4, are investigated using ultrafast transient X‐ray diffraction as a function of optical excitation fluence to discern structural dynamics. Both powder X‐ray diffraction and time‐resolved photoluminescence linewidths narrow over 1 ns following optical excitation for the fluence range studied, concurrent with slight redshifting of the optical bandgaps. These observations are attributed to transient relaxation and ordering of distorted lead iodide octahedra stimulated mainly by electron–hole pair creation. The c axis expands up to 0.37% over hundreds of picoseconds; reflections sampling the a and b axes undergo one tenth of this expansion with the same timescale. Post‐photoexcitation appearance of the (110) reflection in (BA)2 PbI4 would suggest a transient phase transition, however, through new single‐crystal XRD, reflections are found that violate glide plane conditions in the reported Pbca structure. The static structure space group is reassigned as P 21 21 21 . With this, a nonequilibrium phase transition is ruled out. These findings offer increased understanding of remarkable lattice response in 2D perovskites upon excitation. Abstract : Nonequilibrium structures of 2D perovskites are studied using ultrafast X‐ray diffraction. Diffraction peaks post‐photoexcitation increase in intensity and narrow over 1 ns, suggesting an increase in long‐range order within the lead iodide octahedra. These results are corroborated using ultrafast photoluminescence, which shows redshifting and narrowing of photoluminescence peaks on the same timescale as transient X‐ray diffraction.